A qualitative study of hospital pharmacists and antibiotic governance: negotiating interprofessional responsibilities, expertise and resource constraints. Issue 1 (December 2015) - Broom, Alex; Plage, Stefanie; Broom, Jennifer; Kirby, Emma; Adams, Jon
Abstract Background Antibiotic treatment options for common infections are diminishing due to the proliferation of antimicrobial resistance (AMR). The impact of Antimicrobial Stewardship (AMS) programs seeking to preserve viable antibiotic drugs by governing their use in hospitals has hitherto been limited. Pharmacists have been delegated a critical role in antibiotic governance in AMS teams within hospitals but the experience of pharmacists in influencing antibiotic use has received limited attention. In this study we explore the experiences of pharmacists in antibiotic decision-making in two Australian hospitals. Methods We conducted 19 semi-structured interviews to explore hospital-based pharmacists' perceptions and experiences of antibiotic use and governance. The analysis was conducted with NVivo10 software, utilising the framework approach. Results Three major themes emerged in the pharmacist interviews including (1) theresponsibilities of pharmacy in optimising antibiotic use and the interprofessional challenges therein; (2) the importance of antibiotic streamlining and theconstraints placed on pharmacists in achieving this; and (3) the potential, but often under-utilisedexpertise, pharmacists bring to antibiotic optimisation. Conclusions Pharmacists have a critical role in AMS teams but their capacity to enact change is limited by entrenched interprofessional dynamics. Identifying how hospital pharmacy's antibiotic gatekeeping is embedded in the interprofessional nature of clinical decision-making and limited by organisational environment has important implications for the implementation of hospital policies seeking to streamline antibiotic use. Resource constraints (i.e. time limitation and task prioritisation) in particular limit the capacity of pharmacists to overcome the interprofessional barriers through development of stronger collaborative relationships. The results of this study suggest that to enact change in antibiotic use in hospitals, pharmacists must be supported in their negotiations with doctors, have increased presence on hospital wards, and must be given opportunities to pass on specialist knowledge within multidisciplinary clinical teams.